Penyerobotan Tanah Secara Tidak Sah Dalam Perspektif Pidana - Margie Gladies Sopacua (Criminal of Law Department, Faculty of Law, Pattimura University, 2019)
Land of is a very valuable asset, given the price of land is very stable and continue to rise along with the times. Unauthorized land grabbing can harm anyone even more so if the land is used for business purposes. Annexation of land by a person or group of people against another people's land can be interpreted as an act of mastering, occupy or take over someone else's land unlawfully, against the right, or in violation of applicable laws. Therefore, such actions may be sued under civil law or prosecuted under criminal law. Provisions in criminal law contained in Section 363, 365, 167 and 389, 170, 406, 412, 263, 264, 266 as Lex Generalis later in Article 2 of Law No. 51 PRP of 1960 on the Prohibition of Use of Land Without Permission Eligible or the attorney as Lex Specialist.